THE EFFECT OF DEBT POLICY ON COMPANY VALUE WITH DIVIDEND POLICY AS INTERVENING VARIABLE - Lalu Muhammad Syahril Majidi; Endah Tri Wahyuningtyas; Muis Murtadho (SENTRALISASI, 2023)
In carrying out its activity, company requires capital since capital is a crucial element in a company. To gain such capital, company can apply several approaches such as issuing shares or by way of indebtedness to a third party. Those two strategies would bring consequences in form of dividend that is given to the stakeholder on the return of investment that has been invested. The purpose of this study is to test whether the company’s debt policy has an impact on the value of the company with the dividend policy as the intervening variable. This research method uses a quantitative approach while the data analysis used is path analysis to measure the effect of debt policy on dividend policy and its effect on company value. The results showed that the company's debt policy negatively affects the company's dividend policy, the debt policy has a positive impact on increasing the company's value and the dividend policy has a positive and significant effect on the company's value.